Nitrogen-Doped Carbon Dots Induced Enhancement in CO2 Sensing Response From ZnO–Porous Silicon Hybrid Structure - Ramos-Ramón, Jesús A.; Bogireddy, Naveen K. R.; Giles Vieyra, Jorge Arturo; Karthik, Tangirala V. K.; Agarwal, Vivechana (Frontiers in Chemistry, 2020)
In this study, we report a simple method for the fabrication of carbon dots sensitized zinc oxide–porous silicon (ZnO–pSi) hybrid structures for carbon dioxide (CO2) sensing. A micro-/nanostructured layer of ZnO is formed over electrochemically prepared pSi substrates using a simple chemical precipitation method. The hybrid structure was structurally and optically characterized using scanning electron microscopy, X-ray diffraction, fluorescence, and cathodoluminescence after the incorporation of hydrothermally prepared nitrogen-doped carbon dots (NCDs) by drop casting. With respect to the control sample, although all the devices show an enhancement in the sensing response in the presence of NCDs, the optimal concentration shows an increase of 37% at an operating temperature of 200°C and a response time <30 s. The increment in the CO2-sensing response, upon the addition of NCDs, is attributed to an increase in CO2-oxygen species reactions on the ZnO surface due to an increment in the free electron density at the metal–semiconductor-type junction of NCD clusters and ZnO micro-/nanorods. A significant increase in the sensing response ( 24%) at low operating temperature (100°C) opens the possibility of developing very large-scale integrable (VLSI), low operational cost gas sensors with easy fabrication methods and low-cost materials.